Production Performance of Broiler Chicken as Affected by Supplementation of Salts of Organic Acids - ., Vinus; Akbar, M. A.; Tewatia, B. S. (Indian Journal of Animal Nutrition, 2017)
A total of 300, day old commercial broiler chicks were randomly distributed into five treatments having six replicates consisting of ten birds each to assess the efficacy of salts of organic acids as feed additives on growth performance of broiler chicken. A maize-soybean based diet was used as the basal diet (Control group). The basal diet was supplemented with sodium butyrate and calcium propionate @ 0.5 and 1% each. Addition of calcium propionate at 1% level resulted in higher (P